Some Properties of the Essential Fuzzy and Closed Fuzzy Submodules - Marhon, Hassan K.; Khalaf, Hatam Y. (Iraqi Journal of Science, 2020)
In this paper, we introduce and study the essential and closed fuzzy submodules of a fuzzy module X as a generalization of the notions of essential and closed submodules. We prove many basic properties of both concepts.